Sparing Organs at Risk with Simultaneous Integrated Boost Volumetric Modulated Arc Therapy for Locally Advanced Non-Small Cell Lung Cancer: An Automatic Treatment Planning Study - Wang D; Chen J; Zhang X; Zhang T; Wang L; Feng Q; Zhou Z; Dai J; Bi N (Cancer Management and Research, 2020)
Daquan Wang,1,* Jiayun Chen,1,* Xiaodong Zhang,2 Tao Zhang,1 Luhua Wang,1 Qinfu Feng,1 Zongmei Zhou,1 Jianrong Dai,1 Nan Bi1 1Department of Radiation Oncology, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 2Department of Radiation Oncology, The University of Texas MD Anderson Cancer Center, Houston, TX, USA*These authors contributed equally to this workCorrespondence: Nan BiDepartment of Radiation Oncology, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, No. 17 Panjiayuannanli, Chaoyang District, Beijing 100021, People’s Republic of ChinaTel +86 10 87788995Email binan_email@163.comBackground: The technique of simultaneous integrated boost volumetric modulated arc therapy (SIB-VMAT) has been widely used in locally advanced non-small cell lung cancer; however, its dosimetric advantages are seldom reported. This study aimed to quantify dosimetric advantages of SIB-VMAT.Methods: Forty patients with stage III non-small cell lung cancer in our hospital were retrospectively included. SIB-VMAT and conventional VMAT (C-VMAT) plans were generated for every patient using the automatic treatment planning system. A reduced dose was delivered to PTV in SIB-VAMT plans compared to C-VMAT plans (50.4Gy vs 60Gy). The prescribed dose was 50.4 Gy in 28 fractions to PTV and 59.92 Gy in 28 fractions to PGTV in SIB-VMAT plans, while 60 Gy in 30 fractions to PTV in C-VMAT plans. Dose-volume metrics of PTV, total lung, heart, esophagus and spinal cord were recorded. The quality score was used to evaluate organs at risk (OAR) protection for two type prescription plans.Results: Conformal coverage of the targets (PGTV/PTV) by 95% of the prescription dose was well achieved in radiation plans. SIB-VMAT plans achieved significantly higher quality score than C-VMAT plans (Mean: 68.15± 13.32 vs 49.15± 13.35, P< 0.001). More plans scored above sixty in SIB-VMAT group compared to C-VMAT group (72.5% vs 20%, P< 0.001). Notable reductions in mean dose, V30, V40 and V50 of total lung were observed in SIB-VMAT plans compared to C-VMAT plans, with median decreased proportions of 6.5%, 8.7%, 19.6% and 32.1%, respectively. Statistically significant decrease in heart V30 and V40 was also achieved in SIB-VMAT plans, with median decreased proportions of 26.1% and 38.8%. SIB-VMAT plans achieved significant reductions in the maximum doses to both esophagus and spinal cord. Patients with CTV/(GTV+GTVnd) ≥ 8.6 showed more notable decrease in total lung V50 (median, 33.6% vs 28.8%, P=0.001) in SIB-VMAT plans compared to those with the ratio being less than 8.6.Conclusion: SIB-VMAT technique could lead to a substantial sparing of normal organs, including lung, heart, esophagus and cord, mainly through reducing high and inter-median dose exposure. Patients with CTV/(GTV+GTVnd) ≥ 8.6 might benefit more from SIB-VMAT.Keywords: lung cancer, simultaneous integrated boost, radiotherapy, automatic planning, organ at risks